1999
DOI: 10.1007/s002530051554
|View full text |Cite
|
Sign up to set email alerts
|

Production of functional human α 1 -antitrypsin by plant cell culture

Abstract: Recombinant human alpha 1-antitrypsin (rAAT) was expressed and secreted from transgenic rice cell suspension cultures in its biologically active form. This was accomplished by transforming rice callus tissues with an expression vector, p3D-AAT, containing the cDNA for mature human AAT protein. Regulated expression and secretion of rAAT from this vector was achieved using the promoter, signal peptide, and terminator from a rice alpha-amylase gene Amy3D. The Amy3D gene of rice is tightly controlled by simple sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 1 publication
6
69
0
1
Order By: Relevance
“…Cleavage of the RCL at 354 E has been found to be typical of the lysosomal Cys proteinase cathepsin L (Johnson et al, 1986) and nontarget Ser proteases (Nelson et al, 1998). Considerable amounts of truncated protein were also obtained in previous attempts to express recombinant A1AT in rice (Oryza sativa) cells (Terashima et al, 1999;Huang et al, 2001;Trexler et al, 2002;McDonald et al, 2005), N. benthamiana (Sudarshana et al, 2006), and Nicotiana tabacum chloroplasts (Nadai et al, 2009). Nevertheless, A1AT produced in transgenic tomato (Solanum lycopersicum) plants does not show degradation (Jha et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage of the RCL at 354 E has been found to be typical of the lysosomal Cys proteinase cathepsin L (Johnson et al, 1986) and nontarget Ser proteases (Nelson et al, 1998). Considerable amounts of truncated protein were also obtained in previous attempts to express recombinant A1AT in rice (Oryza sativa) cells (Terashima et al, 1999;Huang et al, 2001;Trexler et al, 2002;McDonald et al, 2005), N. benthamiana (Sudarshana et al, 2006), and Nicotiana tabacum chloroplasts (Nadai et al, 2009). Nevertheless, A1AT produced in transgenic tomato (Solanum lycopersicum) plants does not show degradation (Jha et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Plant suspension cultured cells provide a fast system for producing secondary metabolites, biologically active recombinant proteins and antibodies (Francisco et al, 1997;Terashima et al, 1999;Torres et al, 1999). The recombinant proteins expressed can either be transported to subcellular organelles or be secreted into extracellular space via the default pathway in plant suspension cultured cells (Denecke et al, 1990;Liu et al, 1997).…”
Section: Recombinant Protein Expression Using Plant Suspension Culturesmentioning
confidence: 99%
“…For rice cell culture, Trexler et al [16] reported doubling time of 1.5 ~ 1.7 days for a transgenic rice cell culture expressing human 1 -antitrypsin. Terashima et al [15], on the other hand, reported a very long doubling time of 6-7 days in their transgenic rice cell cultures expressing human 1 -antitrypsin. Maximum specific oxygen uptake rate was 0.78 ~ 0.84 mmol O 2 /(gdw h) in the transgenic rice cell culture reported by Trexler et al [16]; 0.4 ~ 0.5 mmol O 2 /(gdw h) for the transgenic tobacco NT-1 cells expressing GUS [53].…”
Section: Growth Rate Oxygen Demand and Metabolic Heat Loadsmentioning
confidence: 97%
“…A number of inducible promoters have been used for expressing recombinant proteins in plant suspension cultures. The rice -amylase (RAmy3D) promoter which is induced by sugar starvation was used in rice cell cultures to express recombinant 1 -antitrypsin [15,16] and recombinant hGM-CSF [5]; the Arabidopsis thaliana heat-shock (HSP18.2) promoter [60], the tomato light inducible rbcS promoter [61], the methyl jasmonate inducible potato cathepsin D inhibitor (CDI) promoter [59], the glucocorticoid-inducible GVG promoter [62], the sweet potato oxidative stress-inducible peroxidase (POD) promoter [63], and the abscisic acid, tetracycline, and copper inducible promoters [64], have all been examined in tobacco cell cultures for recombinant protein production. In order to optimize the efficiency of an inducible gene expression system, it is necessary to examine the inducer concentration and timing of inducer addition.…”
Section: Characteristics Of Recombinant Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation